Heterogeneous biomimetic aerobic synthesis of 3-iodoimidazo[1, 2-a]pyridines via CuOx/OMS-2-catalyzed tandem cyclization/iodination and their late-stage functionalization. Issue 1 (11th September 2014) - Meng, Xu; Yu, Chaoying; Chen, Gexin; Zhao, Peiqing
Abstract : Heterogeneous catalysis performs well in biomimetic oxidation to generate a low-energy pathway for the synthesis of 3-iodoimidazo[1, 2- a ]pyridines. Abstract : In the presence of copper supported on manganese oxide-based octahedral molecular sieves OMS-2 (CuO x /OMS-2), the heterogeneously catalytic, aerobic synthesis of 3-iodoimidazo[1, 2- a ]pyridines from acetophenones, 2-aminopyridines and I2 via tandem cyclization/iodination in a one-pot manner is achieved. As a heterogeneous catalyst, OMS-2 acts not only as a support for catalytic Cu species but also as an electron-transfer mediator (ETM), which combines with Cu to generate a low-energy pathway for rapid electron transfer. In this way, the biomimetic, catalytic oxidation could directly employ air as a green terminal oxidant under mild conditions, and provide corresponding products with broad substrates in moderate to excellent yields using very low catalyst loading (0.2 mol% Cu). In this process, I2 not only plays the role of catalyst for the initial cyclization, with assistance from CuO x /OMS-2, but also acts as a reactant for the next electrophilic oxidative iodination, which makes the reaction highly atom economic. Besides, the late-stage functionalization of the I-substituted imidazo[1, 2- a ]pyridines is also demonstrated by various coupling reactions, which show its potential applications in synthetic and pharmaceutical chemistry. Moreover, the catalyst is truly heterogeneous and reusable.